2014
DOI: 10.3233/jad-132558
|View full text |Cite
|
Sign up to set email alerts
|

Determinants, MRI Correlates, and Prognosis of Mild Cognitive Impairment: The Rotterdam Study

Abstract: Mild cognitive impairment (MCI) marks a transitional stage between healthy aging and dementia, but the understanding of MCI in the general population remains limited. We investigated determinants, MRI-correlates, and prognosis of MCI within the population-based Rotterdam Study. Firstly, we studied age, APOE-ε4 carriership, waist circumference, hypertension, diabetes mellitus, total and HDL-cholesterol levels, smoking, and stroke as potential determinants of MCI. Determinants were assessed cross-sectionally at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(93 citation statements)
references
References 53 publications
5
88
0
Order By: Relevance
“…In agreement with our findings, a very recent analysis also found that APOE e4 was associated with mild cognitive impairment in the general population [22], and a review of in vivo studies showed that APOE e4 was associated with non-pathological changes in brain physiology, which might predispose to neurodegenerative processes [23], possibly including reduced cognitive performance.…”
Section: Discussionsupporting
confidence: 80%
“…In agreement with our findings, a very recent analysis also found that APOE e4 was associated with mild cognitive impairment in the general population [22], and a review of in vivo studies showed that APOE e4 was associated with non-pathological changes in brain physiology, which might predispose to neurodegenerative processes [23], possibly including reduced cognitive performance.…”
Section: Discussionsupporting
confidence: 80%
“…Classification performance rates of the MCI‐model did not improve over those of the AD‐model or mild‐AD‐model. The incorporation of additional prior, biological knowledge (Rathore et al, ), or other information derived from imaging‐ and nonimaging biomarkers such as cerebrovascular status (De Bruijn et al, ), the load (De Bruijn et al, ; Dong et al, ; Fan et al, ), or location of white matter hyperintensities (McAleese et al, ), cerebral blood flow (Bron et al, ), resting‐state functional MRI (de Vos et al, ; Schouten et al, ), PET‐derived biomarkers (Dukart et al, ; Li et al, ), or additional cognitive assessment scores including measures of cognitive reserve (Allegri et al, ; Moradi et al, ; Vieira, Pinaya, & Mechelli, ; Wang et al, ) may further augment classification accuracy without increasing diagnostic complexity. While cognitive assessment scores would most likely provide a valuable contribution to the detection of MCI (Moradi et al, ; Wang et al, ), we did not consider these for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Study details can be found elsewhere (Ikram et al, ; Ikram et al, ). For the present analysis we selected 682 subjects that were older than 60 years of age, underwent MRI in the period 2002–2005, did not have MRI‐defined cortical infarcts, and had data available for MCI diagnosis (De Bruijn et al, ). Subjects were diagnosed as MCI according to criteria previously derived for the Rotterdam study (Adams et al, ; De Bruijn et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…First, we found stronger effects for amnestic MCI than non-amnestic MCI. Indeed, amnestic MCI is more closely linked to AD pathology than non-amnestic MCI [15]. Second, censoring for dementia did not materially change the risk of cancer after MCI – if anything, the risk slightly attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…MCI was defined as the presence of self-perceived cognitive complaints (defined as at least one of 6 questions on memory and daily functioning) and cognitive impairment as assessed with neuropsychological tests in the absence of dementia, in persons aged ≥60 years [15]. The neuropsychological tests measured memory function (15-word learning test immediate and delayed), information-­processing speed (LDST, Stroop first and second subtask), and executive functioning (LDST, Stroop third subtask, and WFT).…”
Section: Methodsmentioning
confidence: 99%